Pengaruh Buy Back Saham PT Telkom terhadap Dividen Periode 2005 - 2008 - Rusbandi, Natasya; Heykal, Mohamad (Binus Business Review, 2010)
Micro and macro economic condition has negative and positive effect for the financial market and also the investment. Based on that condition, many companies had to do some corporate action which mean investors and also shareholders had to adjust their portfolio for getting their objective. Investors and shareholder will see this corporate action. It includes the investor who wants to buy the companyâs stock. This attention had always related with the dividend payment which will get by the investor, because for the long term investor, or the shareholders, the information about dividend payment is very important for them. When global financial crises happened in 2008, some of the emiten in Indonesia capital market, had donne their corporate action which is the buy back or repurchase stock of their outstanding shares. Some of them is the state owned enterprise, PT TELKOM. Some important thing which related with the buy back is the stock price and also dividend price. With this buy back strategy, it can be seen that PT TELKOM had tried to eliminate any threat with their stock price at that time, or to prevent their stock price become undervalued. Especially in the third quarter in 2008. This strategy had shown succeed because when the global financial crisis happened, TELKOM performance had indicated succeed based on their financial report and also the EPS and DPS every year did not show significance different result.Â